Efektifitas BION (Bintang Online) Dalam Meningatkan Motivasi Belajar Siswa Pada Masa Pandemi Covid 19 di Kelas V SDN 1 Ngembel - Abdillah, Rendra Handy (JURNAL PENDIDIKAN DASAR NUSANTARA, 2020)
Abstract: Learning motivation has very strong correlation with student achievement. If the learning motivation cannot be improved, then the achievement will not be optimal as well. Moreover, the current pandemic time decreases students’ motivation. The use of reward and punishment method is an alternative to raise students’ learning motivation. The purpose of this research was to observe the use of BION (Bintang Online) in improving the learning motivation of 5th grade students in State Elementary School 1 of Ngembel amidst the pandemic where physical distancing is simply a logical consequence. The supporting instruments were (1) observation sheet, (2) questionnaire sheet, (3) documentation photo, and (4) interview sheet. The data were collected using 4 methods: (1) observation, (2) questionnaire, (3) documentation, and (4) interview. The effect of BION medium was fairly positive based on the obtained result. Based on the observation result, the post-cycle, compared to the pre-cycle, had 22% improvements in assignment completion, 27% improvement in punctuality, and 22% improvement in criteria mastery. Another reference came from the questionnaire; in the 3rd point, 100% of the students felt that BION was able to raise their motivation. The interview with the parents, regarding the effect of BION on the students’ intrinsic motivation to learn independently, also showed similar result. Based on these data, it is concluded that BION is effective in improving the students’ learning motivation during the pandemic. Keywords: (BION) Bintang Online, Learning motivation, Reward and Punishmen